Analisis Faktor-Faktor yang Mempengaruhi Kejadian Kista Ovarium pada Wanita Usia Subur di Puskesmas Tlogosari Kulon Semarang - Aprilia Afifah Zahrani; Tutik Rahayu; Sri Wahyuni (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2025)
Ovarian cysts are a type of reproductive disease that often attacks women. Ovarian cysts are collections of fluid in the ovaries or fallopian tubes that accumulate and are surrounded by a membrane formed from the outer layer of the ovaries. Many people, especially women of childbearing age, do not know the factors that cause ovarian cysts themselves. Cyst Factor Analysis aims to increase public knowledge for early prevention. This research is a type of quantitative research using a cross sectional approach. The sample used was 109 respondents and anticipated drop out was 121 respondents in the work area of the Tlogosari Kulon Semarang Health Center. The sample was taken using a probability sampling technique with a simple random sampling type. The comparative test used was the Chi-Square test. The results of research using the Chi-Square test proved that the p value of the ovarian cyst factors was <0.05. This shows that there is a significant and strengthening relationship between age, menstrual cycle, genetic history, parity, economic status, history of previous cysts, menarche, hypothyroidism. There is a relationship between age, menstrual cycle, genetic history, parity, economic status, history of previous cysts, menarche, hypothyroidism on the incidence of ovarian cysts in women of childbearing age at the Tlogosari Kulon Semarang Community Health Center, and factors that have a significant influence are genetic history with a p-value <0.050.